(3JdNjU GdeaJGM aj GdeYGfj hGdHjGfs - (3GdbRhjfj GdOeTbj, CHh GdeYGdj, GdNWjH (B- (3LdGd GdOjf, eMeO Hf YeQ Hf YHO GdQMef, (B739 (3g`s ((3ecI GdecQeIs)
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CfYe hYde ef GdHjGf eG de fYde CeG HYO adeG cGf Yde GdHdGZI hJhGHYgG ef CLd GdYdhe hcGf GdbSe GdKGdK ef eaJGM GdYdhe GdPj Ufag GdScGcj CYXe eG Ufa ajghSejJg JdNjU GdeaJGMs
(3BNQgG (B:s
(3ahGJM GdShQ hNhGJjegG hGQOI Ydi CMSf GdhLhg hCcedgG jXgQ Pdc HGdJCed eY GdJPcQ deG SHbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 192s
(3eYLe GdeDdajf(B: 3 / 396s
(3cTa GdXfhf(B: 1 / 473s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdHdGZIs